2004
DOI: 10.5395/jkacd.2004.29.1.044
|View full text |Cite
|
Sign up to set email alerts
|

Shaping ability of nickel-titaniumrotary files

Abstract: This study compared the shaping ability of nickel-titanium rotary files with different rake angle and radial land.The nickel-titanium files used in this study were Profile(Dentsply, Maillefer, Ballaigues, Switzerland), Hero 642(Micromega, Besancon, France), and K3(SybronEndo, Glendora, Ca, USA) file. Resin blocks substituted for root canals. 36 resin blocks were divided into 3 groups with 12 canals each. The time for canal preparation was recorded. The images of pre-and postoperative resin canal were scanned a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Group H and group P took less instrumentation time significantly than the other groups in both operators. Despite the research that the rake angle affects the shaping time 24) , interestingly, group H did not have significant differences with group P. The result was interpreted that the time lapse was reduced significantly by the use of ProTaper S1 for pre-flaring of coronal two-thirds. Tip diameter of S1 corresponds to ISO size #17, and this made it easy to get not only coronal flaring but also apical preenlargement with the progressive greater taper.…”
Section: ⅳ Discussionmentioning
confidence: 72%
“…Group H and group P took less instrumentation time significantly than the other groups in both operators. Despite the research that the rake angle affects the shaping time 24) , interestingly, group H did not have significant differences with group P. The result was interpreted that the time lapse was reduced significantly by the use of ProTaper S1 for pre-flaring of coronal two-thirds. Tip diameter of S1 corresponds to ISO size #17, and this made it easy to get not only coronal flaring but also apical preenlargement with the progressive greater taper.…”
Section: ⅳ Discussionmentioning
confidence: 72%
“…9 The introduction of nickel-titanium alloy for the mechanically driven endodontic instruments has greatly simplified shaping of the root canal systems. 9,10 Reports have shown that nickel-titanium (Ni-Ti) instruments are two or three times more flexible than conventional stainless steel files and that they have more resistance torsional fracture. 11 Thus, these instruments have been found to be better than stainless steel instruments in maintaining the original anatomy and the shape and position of the apical foramen.…”
Section: Introductionmentioning
confidence: 99%
“…Reports on the efficacy and shaping ability of nickel-titanium rotary files have demonstrated their potential for root canal treatment. [3][4][5][6] Nickel-titanium instruments have a decreased tendency for canal transportation and therefore remain better centered. 7) Most studies have expected that these new instruments may enhance endodontic treatment with respect to both its quality and speed.…”
Section: ⅰ Introductionmentioning
confidence: 99%